Maternal and Child Health Journal - Dye, Timothy; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Maternal and Child Health Journal is the first exclusive forum to advance the scientific and professional knowledge base of the maternal and child health (MCH) field. This bimonthly provides peer-reviewed papers addressing the following areas of MCH practice, policy, and research: MCH epidemiology, demography, and health status assessment Innovative MCH service initiatives Implementation of MCH programs MCH policy analysis and advocacy MCH professional development. Exploring the full spectrum of the MCH field, Maternal and Child Health Journal is an important tool for practitioners as well as academics in public health, obstetrics, gynecology, prenatal medicine, pediatrics, and neonatology. Sponsors include the Association of Maternal and Child Health Programs (AMCHP), the Association of Teachers of Maternal and Child Health (ATMCH), and CityMatCH.
Keywords: Gynecology; Public health; Maternal and child health services; Pediatrics; Population; Sociology; Public Health; Sociology, general; Population Economics; Pediatrics; Gynecology; Maternal and Child Health